2021
DOI: 10.3897/natureconservation.43.62750
|View full text |Cite
|
Sign up to set email alerts
|

The illegal hunting and exploitation of porcupines for meat and medicine in Indonesia

Abstract: Indonesia is home to five species of porcupines, three of which are island endemics. While all five species are currently assessed as Least Concern by the IUCN Red List of Threatened Species, impacts of harvest and trade have not been factored in. To gain a fuller understanding of the porcupine trade in Indonesia, this study examines seizure data of porcupines, their parts and derivatives from January 2013 to June 2020. A total of 39 incidents were obtained amounting to an estimated 452 porcupines. Various con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…18 Porcupine quills, a byproduct of porcupine pork, also have been used for medicinal purposes, such as stomach pains, bleeding and rheumatic disease treatments. 15,17 In addition, porcupine quills are rich in keratin (with 95%) and are regarded as an excellent source of bioactive peptides. 19 Previous studies reported that feather keratin hydrolysate prepared by fermentation showed a significant antioxidant.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…18 Porcupine quills, a byproduct of porcupine pork, also have been used for medicinal purposes, such as stomach pains, bleeding and rheumatic disease treatments. 15,17 In addition, porcupine quills are rich in keratin (with 95%) and are regarded as an excellent source of bioactive peptides. 19 Previous studies reported that feather keratin hydrolysate prepared by fermentation showed a significant antioxidant.…”
Section: Introductionmentioning
confidence: 99%
“…Most research on bioactive peptides with anti‐breast cancer activity has focused on marine species, but little research on terrestrial organisms. Porcupines (Family: hystricidae) mainly inhabit grasslands, deserts, forests, temperate scrub and prairie mountains, and is located in many countries, such as China, Malaysia, India, Congo and Italy 14,15 . Porcupine meat is popular due to its high protein, low fat and low cholesterol, which has further resulted in a rapid increase in the number of porcupine farms 16 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In mammals, there are generally 4 types of digestive systems, namely ruminant and nonruminant foregut fermenter, hindgut fermenter, and autoenzyme-dependent digester (Furness et al 2015). Sunda porcupine (Hystrix javanica) is one of the wild, endemic, and protected animals in Indonesia (van Weers 1979;Gomez 2021). Based on the natural diets of porcupines (Hystricidae and Erethizontidae), they are considered herbivores that consume a variety of browse, grass, bulbs, roots, or fruits (Mori et al 2017).…”
Section: Introductionmentioning
confidence: 99%